MORAL DAN AKHLAQ DALAM PSIKOLOGI MORAL ISLAMI - safrilsyah, safrilsyah; Mohd Yusoff, Mohd Zailani; Othman, Mohd Khairi (Psikoislamedia: Jurnal Psikologi, 2017)
Moral and akhlaq are almost considered the same by some people. Even though they has different meanings. The difference between them becomes interesting to discuss for explain the difference between them, from both the paradigm and the application in the moral psychology. The morals are meaningful as good and bad behavior are based on human consent. In contrast to moral, Akhlaq derived from the word â€œkhulqâ€ is cognate with khalaqa (created). It has the meaning of the inherent nature of the soul (malakah) in a person according to the origin of its creation (ahsanu taqwim) sourced from the essence of the creator (Allah). Therefore it can be sure there are different moral meanings in western society (non-Muslim) with Muslim society. This distinction opens opportunities for discussion of moral psychology in Islamic perspective. This article seeks to review in detail one of the sub-themes of moral psychology namely judgment or moral reasioning, where in terms of Islamic psychology is known by akhlaq judgment (penaakulan akhlaq) from Asmawati Hamzah (2007).